1987
DOI: 10.1677/joe.0.1140119
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide increases intracellular free calcium in rat and human pituitary tumour cells in vitro

Abstract: Prolactin secretion by a human pituitary tumour cell line produced in our laboratory was stimulated by TRH, vasoactive intestinal peptide (VIP) and epithelial growth factor (EGF). All raised the intracellular concentration of free calcium (Ca2+ i) of cells loaded with a fluorescent quinoline Ca2+ indicator in suspension, but the effect of TRH was much more rapid and less prolonged than that of VIP and EGF. Both TRH and VIP also increased Ca2+ i in GH3 rat pituitary tumour cells, but in this cell line the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
(27 reference statements)
3
4
0
Order By: Relevance
“…In the human pituitary tumour cells VIP not only increased prolactin release in vitro (Prysor-Jones et al 1987) but in the present experiments it also increased cell growth. Moreover, the effective concentrations of VIP for increased DNA synthesis were close to that of the maximum concen¬ tration found in rat portal plasma (Shimatsu, Kato, Matushita et al (1981).…”
Section: Modification Of Effects Of Fgf By Oestradiol Pdgf and Egfsupporting
confidence: 65%
See 1 more Smart Citation
“…In the human pituitary tumour cells VIP not only increased prolactin release in vitro (Prysor-Jones et al 1987) but in the present experiments it also increased cell growth. Moreover, the effective concentrations of VIP for increased DNA synthesis were close to that of the maximum concen¬ tration found in rat portal plasma (Shimatsu, Kato, Matushita et al (1981).…”
Section: Modification Of Effects Of Fgf By Oestradiol Pdgf and Egfsupporting
confidence: 65%
“…It may well be, therefore, that there is a stimulatory interaction between oestradiol and VIP on pituitary tumours of man. In contrast with the action of VIP, it was notable that no stimulatory effect of TRH was obtained on cell growth in the same conditions in spite of its ability to release prolactin from these human cells (Prysor-Jones et al 1987). These differences in the effects on cell growth are not surprising since previous experiments have shown that the two peptides act at the cellular level in a different manner.…”
Section: Modification Of Effects Of Fgf By Oestradiol Pdgf and Egfmentioning
confidence: 95%
“…We observed that VIP caused an enhancement of Ca2 + incorporation with a peak at 5 s and lasting for 1 min. Such a finding is consistent with earlier results obtained in rat and human pituitary tumor cells indicating that VIP receptor stimu lation induces an increase of the intracellular Ca2+ concentra tion [19]. The hypothesis which could ensue from these data is that the newly incorporated Ca2+ may act as a positive modu lator of the activity of adenylate cyclase associated to VIP recep tors.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, several growth factors may also modulate both cell growth and PRL production. In agreement with this notion, Elsholz and co-workers (21) (22) claimed that the effect of EGF was depen¬ dent on extracellular calcium. The plasma levels of EGF in humans (19) and mice (20) are 2-6 • 10"1() mol/1.…”
Section: Discussionmentioning
confidence: 69%
“…In agreement with Schonbrunn and co-workers (7) we have shown that EGF increases PRL synthesis and secretion in the GH4Ci cells in a dose-dependent manner. The initial increase in the [Ca2 + ]j after administration of TRH to the GH4C, cells is produced by mobilization of intracellular stores of cal¬ cium (22). Therefore the observed ED50 of ÍO^-IO-10 mol/1 suggests a physiological role for EGF in the regulation of PRL synthesis and secretion.…”
Section: Discussionmentioning
confidence: 95%